2023
DOI: 10.3390/biology12010112
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Impairment Correlates with Executive Functions Disorders and Other Specific Cognitive Dysfunctions in Parkinson’s Disease

Abstract: Introduction. Olfactory and cognitive disorders represent important non-motor symptoms in Parkinson’s disease (PD). No clear evidence was reported about association of specific cognitive domains and olfactory impairment. Objective. The aim of this study was to evaluate the association between olfactory dysfunction and specific cognitive domains in PD patients compared to controls. Methods. 178 PD patients and 98 controls were enrolled and evaluated for odor threshold (OT), discrimination (OD), identification (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Considering these results, our data suggested a potential role of biomarkers for olfactory function in the early diagnosis of mild cognitive impairment. Similarly, other previous studies indicated that olfactory impairment represents a peculiar biomarker in neurodegenerative disorders [ 6 , 7 , 8 , 42 , 43 , 44 , 45 , 46 ]. Recently, there has been an increased interest in the evaluation of olfactory dysfunction in the early stage of neurodegenerative disorders such as Parkinson’s disease.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Considering these results, our data suggested a potential role of biomarkers for olfactory function in the early diagnosis of mild cognitive impairment. Similarly, other previous studies indicated that olfactory impairment represents a peculiar biomarker in neurodegenerative disorders [ 6 , 7 , 8 , 42 , 43 , 44 , 45 , 46 ]. Recently, there has been an increased interest in the evaluation of olfactory dysfunction in the early stage of neurodegenerative disorders such as Parkinson’s disease.…”
Section: Discussionsupporting
confidence: 65%
“…Recently, there has been an increased interest in the evaluation of olfactory dysfunction in the early stage of neurodegenerative disorders such as Parkinson’s disease. In our previous study on Parkinson’s disease, patients’ significant correlations were observed between OT and language, between OD and visuospatial domain, and between OI and executive index scores and attention [ 6 ], suggesting that the OT, OD, and OI are differently related to the cognitive abilities of the subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 10% of subjects with idiopathic loss of smell receive a diagnosis of PD within 10 years ( 10 ). Olfactory dysfunction is associated with male sex and non-motor manifestations such as apathy ( 11 ) and cognitive dysfunction ( 12 ). However, the relationship between olfactory and autonomic dysfunction is unclear, and its investigation may be worthwhile in light of the proposed “brain-first” and “body-first” models of disease progression.…”
Section: Introductionmentioning
confidence: 99%